Základní umělecká škola - Klimšová, Barbora (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Téma diplomové práce je novostavba Základní umělecké školy. Objekt se nachází v intravilánu města Hronova. Objekt je členěn na dvě křídla. V jedné části objektu v 1 NP se nachází převážně jednotlivé učebny pro hru na individuální hudební nástroj. Ve druhé části objektu se nachází koncertní sál, který je určený pro zkušebnu orchestrální hry. Ve 2 NP se nachází převážně jednotlivé učebny. Ve 3 NP je navržen taneční a baletní sál a jednotlivé učebny. V podkroví je učebna pro výtvarnou výchovu. Objekt je částečně podsklepený. Budova je zasazena na rovinném pozemku. Objekt je zděný ze systému LIAPOR, stropní konstrukce jsou provedeny z panelů SPIROLL, v suterénu z ŽB desky. Konstrukce střechy je řešena jako dvouplášťová, nosná konstrukce krovu vaznicová a hambálková, střechy provedeny jako sedlové se sklonem 35 °.

The final thesis is new building Basic school of art and music. The building is located in the urban area of Hronov. The building is divided into two wings. In one part of the building at 1 NP is mainly individual classrooms for play on an individual instrument. In the second part of the building is the concert hall, which is designed for orchestral rehearsal. The 2nd floor is mostly individual classrooms. In 3 NP is designed dance and ballet hall and individual classrooms. In the attic is a classroom for art education. The building has a partial basement. The building is planted on flat land. The building is brick from the system LIAPOR, overhead structures are made of panels SPIROLL, in the basement of a reinforced concrete slab. The roof construction is designed as a purlin roof and „hambalek“ purlin roofs made as saddle with a slope of 35 degrees.
Basic School of Art and Music
Keywords: Základní umělecká škola; zděný systém LIAPOR; strop SPIROLL; sedlová střecha; nosná konstrukce krovu vaznicová a hambálková; střešní krytina - maloformátová plechová; Basic school of art and music; masonry systém; ceiling SPIROLL; saddle roof; the roof construction is designed as a purlin roof and „hambalek“ purlin roofs; roof covering of small format - metal roofing